An Epidemic of Pediatric HIV From Reuse of Infusion Equipment in Pakistan. (1st February 2022) - Syed, Muhammad Asif; Khan, Adnan; Chaudhry, Ambreen; Baig, Mirza Amir; Memon, Naveed Masood; Kumar, Santosh; Bhurt, Saeed Ahmed; Qadri, Munaza; Vighio, Anum; Baig, Zeeshan Iqbal; Rabold, Elizabeth M.; Ali, Hammad; et al.
Abstract : Background: From April to June 2019, a total of 909 new HIV infections were identified in Larkana, Pakistan; 86% was children younger than 15 years. To identify the possible transmission links in this outbreak, a case–control study was conducted in June 2019. Methods: For cases, we selected a systematic random sample of 100 HIV-positive children from the screening list. We chose 2 age-matched and sex-matched controls from the neighborhood of each HIV-positive case. All selected children were tested using the World Health Organization–approved rapid diagnosis test algorithm. We interviewed the parents of each selected child about previous exposures to parenteral treatment and compared exposures of case and control children using conditional logistic regression. Results: The ages of the selected children ranged from 1 month to 10 years. More than 90% of both HIV+ and HIV− children had received outpatient health care from MBBS-qualified private physicians. Eighty-three percent of HIV+ children versus 46% of HIV− children had received health care from one private physician [adjusted odds ratio (aOR) = 29, 95% confidence interval (95% CI): 10 to 79]. Intravenous infusions during the last outpatient visit were reported by 29% of case versus 7% of controls (aOR 57, 95% CI: 2.9 to >1000), whereas no case children and 17% of control children had received only intramuscular injections (aOR 0, 95% CI: 0 to 41). Among cases, 94% had been given infusions through a drip set compared with 85% of control children (aOR = 7.7, 95% CI: 2.3 to 26). Infusions had been administered with reused IV drip sets in 70% of cases compared with 8% of controls (aOR = 197, 95% CI: 16 to 2400). Discussion: Private physicians reusing intravenous drip sets to treat outpatients seen in private practice were responsible for this HIV epidemic. Mapping and regulation of private practitioners were suggested. Abstract : Supplemental Digital Content is Available in the Text.